Antiprotozoal Activity of Ethanol Extracts of Some Bomarea Species (2008)
ABSTRACT: The antiprotozoal activity of 26 ethanol extracts derived from 13 species of the genus Bomarea (Alstroemeriaceae) were evaluated against the promastigote forms of three Leishmania species (L. amazonensis L.,L. braziliensis Vianna, and L. donovani Laveran & Mesnil) and the epimastigote form of Trypanosoma cruzi Chagas. IC50 values for leishmanicidal activities were between 4.9 and 98.6 μg/mL, B. setacea extracts being the most active against the three species of Leishmania. Amphotericin B (IC50 = 0.2 μg/mL) and pentamidine (IC50 = 10 μg/mL) were used as control in this assay. IC50 values for antitrypanosomal activities were between 65.2 and 92.7 μg/mL, whereas the control benznidazole had an IC50 value of 2 μg/mL.